Cryopreservation of African painted dog (Lycaon pictus) ovarian tissue - Hartzler, Kate E.; McCartney, Chiara; Songsasen, Nucharin; Nagashima, Jennifer B. (Frontiers in Veterinary Science, 2023)
Development of techniques for the preservation and use of gonadal tissues are increasingly needed for the genetic management of the endangered African painted dog (Lycaon pictus). Here we evaluated cryopreservation techniques for ovarian tissue (2x2x1 mm3 fragments, n = 11 individuals): needle immersed vitrification (NIV), with equilibration in a 7.5% DMSO and 7.5% ethylene glycol solution, and vitrification in a 15% DMSO, 15% ethylene glycol, and 0.5M sucrose solution, and slow freezing in cryovials with either the equilibration (SF-E) or vitrification (SF-V) solutions. Following warming, tissues were either fixed and embedded for evaluation of density of morphologically normal follicles (n = 11), semi-quantitative scoring of stromal cell preservation, and apoptotic index (TUNEL stain, n = 8), and/or flash-frozen for expression of proliferation (PCNA), apoptosis (CASP3, BCL2), or oxidative stress (GPX3, SOD1, SOD2) pathway genes (n=4). Needle immersed vitrification maintained higher density of morphologically normal follicles than the slow freezing protocols applied (p<0.05), with no significant changes in expression of selected genes among treatment groups. A slight increase in apoptotic index was observed in all cryopreservation groups, but only reached significance in SF-E compared with fresh tissue controls (p<0.05). Future research should be dedicated to developing improved methods for ovarian tissue culture in the species, both as a means to evaluate the efficacy of tissue cryopreservation techniques and for the production of viable oocytes from banked ovarian tissue in the endangered African painted dog.